CRIMINOLOGICAL ANALYSIS OF INDICATORS OF CRIMES AGAINST THE NATIONAL SECURITY’S FUNDAMENTALS OF UKRAINE - Sysoieva, Victoriya; Zubko, Yevheniy (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: the purpose of scientific research is to determine the state, trends and structure of crimes against the foundations of national security of Ukraine in recent years. Methods: general scientific and special scientific methods were used in the preparation of the scientific article, including statistical, formal-logical, system-structural, documentary, generalization method, etc. Results: the article analyzes the quantitative, qualitative and quantitative indicators of crimes against the foundations of national security of Ukraine. The main tendencies of these crimes are highlighted. The exceptional importance and necessity of counteracting these crimes is emphasized. Discussion: the article is devoted to the analysis of the state, tendencies and structure of crimes against the foundations of national security of Ukraine in recent years. The most common crimes of this type are highlighted. The statistical indicators of these crimes for the last 5 years are generalized. According to the statistical information of the Report on Registered Criminal Offenses and the results of their pre-trial investigation, crimes against the foundations of national security are not very common in our country. Prior to the military confrontation, only a few cases of such crimes were registered. In addition, the dynamics of crimes against the foundations of national security during this period is unstable. Among all the analyzed crimes, according to statistical data, the most registered are qualified under Art. 110 of the Criminal Code of Ukraine («Encroachment on the territorial integrity and inviolability of Ukraine») and under Art. 111 of the Criminal Code of Ukraine («Treason»). In total, these crimes account for more than 60% of all reported crimes against the foundations of Ukraine’s national security. The structure of crimes against the foundations of Ukraine’s national security is dominated by particularly serious and grave crimes. In recent years, the number of reported particularly serious crimes in this category has increased significantly, which confirms the existence of a real and very serious threat to the national security of our country.